Enhanced Vertical Mixing in Coastal Upwelling Systems Driven by Diurnal‐Inertial Resonance: Numerical Experiments. Issue 9 (6th September 2020) - Fearon, Giles; Herbette, Steven; Veitch, Jennifer; Cambon, Gildas; Lucas, Andrew J.; Lemarié, Florian; Vichi, Marcello
Abstract: The land‐sea breeze is resonant with the inertial response of the ocean at the critical latitude of 30°N/S. 1‐D vertical numerical experiments were undertaken to study the key drivers of enhanced diapycnal mixing in coastal upwelling systems driven by diurnal‐inertial resonance near the critical latitude. The effect of the land boundary was implicitly included in the model through the "Craig approximation" for first‐order cross‐shore surface elevation gradient response. The model indicates that for shallow water depths (<∼100 m), bottom shear stresses must be accounted for in the formulation of the "Craig approximation, " as they serve to enhance the cross‐shore surface elevation gradient response, while reducing shear and mixing at the thermocline. The model was able to predict the observed temperature and current features during an upwelling/mixing event in 60 m water depth in St Helena Bay (∼32.5°S, southern Benguela), indicating that the locally forced response to the land‐sea breeze is a key driver of diapycnal mixing over the event. Alignment of the subinertial Ekman transport with the surface inertial oscillation produces shear spikes at the diurnal‐inertial frequency; however their impact on mixing is secondary when compared with the diurnal‐inertial resonance phenomenon. The amplitude of the diurnal anticyclonic rotary component of the wind stress represents a good diagnostic for the prediction of diapycnal mixing due to diurnal‐inertial resonance. The local enhancement of this quantity over St Helena Bay provides strong evidence for the importance of the land‐sea breeze in contributing to primary production in this region through nutrient enrichment of the surface layer. Plain Language Summary: Winds near the coast often have a daily cycle known as the land‐sea breeze. Near latitudes of 30°N/S ubiquitous rotating ocean currents also have a daily frequency and therefore become enhanced by daily winds at these latitudes. The ocean currents result in vertical mixing of subsurface and surface water layers, bringing subsurface nutrients to the surface where they stimulate phytoplankton growth. In this study we use a simple model of the ocean (composed of the vertical dimension only) to study the key drivers of vertical mixing due to the land‐sea breeze. We show how vertical mixing is reduced in shallow water (<∼100 m) near the coast, where currents are slowed down by friction at the seabed. We find that vertical mixing can be predicted by a parameter computed from wind speed and direction over time. This parameter is shown to be enhanced over St Helena Bay on the west coast of South Africa, where phytoplankton blooms are known to be particularly prevalent. The results suggest that the land‐sea breeze is likely to be an important contributor to phytoplankton bloom development in this region. Similar processes are likely to be at play in other coastal regions. Key Points: Land‐sea breeze driven vertical mixing is studied using a 1‐D model including the land boundary effect The land boundary effect dampens vertical mixing, particularly when bottom friction is nonnegligible The diurnal anticyclonic rotary component of the wind stress provides a diagnostic for diapycnal mixing